Los derechos fundamentales en la España del siglo XX - Varela Suanzes-Carpegna, Joaquín (Teoría y Realidad Constitucional, 2007)
In this article I will study the idea, and especially the legal regulation and the real aplication of the constitutionnal rights in Spain during the XXth century. The main object of the article is giving a short and clear synthesis about this subject. I will mainly analyze two basic ideas: the content of the fundamental rights, in accordance with the classic distinction between civil, political and social rights; and the form used to protect those rights, that will require to study its legal aplication by courts, and its guarantees opposite of the legislative and executive powers.